The Motivational Pattern of Attitude Formation within the Functional Approach: With reference to first time voters in the University of Colombo - Chandrasekara, Ruwangi; Dharmadasa, M.P.P. (University of Colombo, 2011)
While attitude formation and change remains a significant element in the pursuit of PDUNHWLQJ WRGD\¶V SROLWLFDOPDUNHWHUV DUH VXFFHVVIXOO\ GULYLQJ YDULRXVPDUNHWV RIWDUJHW voters towards favourable attitude change. The first time voter group is an important target